2020
DOI: 10.1007/s11661-020-06037-z
|View full text |Cite
|
Sign up to set email alerts
|

As-Built and Post-treated Microstructures of an Electron Beam Melting (EBM) Produced Nickel-Based Superalloy

Abstract: The microstructures of an electron beam melted (EBM) nickel-based superalloy (Alloy 718) were comprehensively investigated in as-built and post-treated conditions, with particular focus individually on the contour (outer periphery) and hatch (core) regions of the build. The hatch region exhibited columnar grains with strong 〈001〉 texture in the build direction, while the contour region had a mix of columnar and equiaxed grains, with no preferred crystallographic texture. Both regions exhibited nearly identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
(55 reference statements)
0
9
0
1
Order By: Relevance
“…Thanks to the vacuum environment and the preheating step, the typical working temperature during an EB-PBF is high, and it ranges, e.g. between 700 °C [58,59] and 1050 °C [59][60][61][62] for titanium alloys.…”
Section: Sintering During Eb-pbfmentioning
confidence: 99%
“…Thanks to the vacuum environment and the preheating step, the typical working temperature during an EB-PBF is high, and it ranges, e.g. between 700 °C [58,59] and 1050 °C [59][60][61][62] for titanium alloys.…”
Section: Sintering During Eb-pbfmentioning
confidence: 99%
“…Niobium segregation during high-temperature process leads to the formation of Laves phase known to be detrimental to the material strength and ductility, by depleting the principal elements needed for precipitation strengthening (Qi et al, 2009;Parimi et al, 2014). The microstructure of AM IN718 has been investigated in quite a few studies (Hosseini and Popovich, 2019;Deng, 2019;Qi et al, 2009;Deng et al, 2018;Goel et al, 2020;Murr et al, 2011;Parimi et al, 2014;Goel, 2020;Strondl et al, 2011;Lu et al, 2015). The presence of phases discussed above are confirmed in AM IN718 parts as well.…”
Section: Discussionmentioning
confidence: 86%
“…Goel et al showed that HIP and HIP 1 HT lead to significant reduction of defects including porosities and lack of fusion (Goel et al, 2018a). It is also reported that HIPing completely dissolve the d phase present in the as-built parts, leading to grain growth (Goel et al, 2020). HIP 1 HT increase the hardness for PBF-EB samples compared to the as built parts owing to precipitation of g 0 0 (Goel et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Precipitates in the as-built IN718 alloy included γ , γ", δ, TiN and NbC [112]. The alloy built using a contour scanning strategy showed a higher density of fine carbides than the one fabricated using the hatch scanning strategy; the difference is negligible after appropriate heat treatment [119]. An increase in grain width and precipitation coarsening was found as the distance from build table increased [109,116].…”
Section: Microstructural Characterization Of Powder Bed Fusion Additive Manufactured Ni Alloys Electron Beam Processed Ni Alloysmentioning
confidence: 94%